2002
DOI: 10.1038/sj.ejcn.1601407
|View full text |Cite
|
Sign up to set email alerts
|

The effect of guar gum addition to a semisolid meal on appetite related to blood glucose, in dieting men

Abstract: Objective: To investigate whether addition of modified guar gum (GG) to a low-energy semisolid meal might be effective on appetite by modifying the response of blood glucose and other blood parameters. Design: Three intervention periods of 2 weeks each, separated by washout periods of 4 weeks. Randomized and cross-over design. Subjects: Fifteen overweight male subjects (mean AE s.d.; age, 44 AE 9 y; body mass index, 28.6 AE 1.8 kg=m 2 ). Intervention: Subjects consumed a low-energy diet divided over three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Astrup et al (1990) and Quaade et al (1990) reported lower hunger scores when the energy-restricted diet was supplemented with 30 g of fibre per day, whereas Kovacs et al (2001) and Kovacs et al (2002) observed no such effect.…”
Section: Dietary Fibrementioning
confidence: 98%
See 2 more Smart Citations
“…Astrup et al (1990) and Quaade et al (1990) reported lower hunger scores when the energy-restricted diet was supplemented with 30 g of fibre per day, whereas Kovacs et al (2001) and Kovacs et al (2002) observed no such effect.…”
Section: Dietary Fibrementioning
confidence: 98%
“…Based on available evidence on bowel function, the Panel considered dietary fibre intakes of 25 g/day to be adequate for normal laxation in adults on an habitual diet (EFSA NDA Panel, 2010a). Dietary fibre doses of around 7-30 g/day with total diet replacements for weight control have been reported Quaade et al, 1990;Kovacs et al, 2001;Kovacs et al, 2002). Often the amount is individually determined.…”
Section: Dietary Fibrementioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, in a separate study we found that addition of the same modi®ed GG to a low-energy semisolid meal resulted in a more moderate change in blood glucose and insulin after meal ingestion. 41 This may result in a prolonged feeling of satiety. 16 Evidence for long-term weight maintenance with dietary ®ber has been presented by a study by Hamilton and Anderson.…”
Section: Discussionmentioning
confidence: 99%
“…Meals dense in fiber have also been demonstrated to be able to control the sense of hunger, satiety, inhibit the desire for another meal, or induce satiation, limit the size of the meal, possibly by lowering caloric density or slowing down gastric emptying [40,129] This would further decrease the sugar load of the individual, since high-fiber diets usually have a lower glycemic load.…”
Section: Polydextrose As a Satiety Increasing Agentmentioning
confidence: 99%